Synthesis of aspartate transcarbamoylase in Escherichia coli: transcriptional regulation of the pyrB-pyrI operon. - Navre, M (1983)
The first committed reaction in pyrimidine biosynthesis in Escherichia coli and Salmonella typhimurium is catalyzed by the allosteric enzyme aspartate transcarbamoylase (aspartate carbamoyltransferase; carbamoylphosphate:L-aspartate carbamoyltransferase, EC 2.1.3.2), the product of the pyrB-pyrI operon. Regulation of the pyrimidine pathway is achieved in part by changes in the enzyme's catalytic activity as a function of the concentration of substrates and other metabolites as well as by variations in enzyme synthesis in response to changes in cellular levels of pyrimidine nucleotides. Although there is substantial evidence that UTP concentration has a marked influence on expression of the pyrB-pyrI operon, the mechanism of this control is not known. We have cloned the operon and determined the nucleotide sequence of the region preceding the first structural gene (pyrB). These studies show two regions sharing considerable homology with the consensus sequence of E. coli promoters, a segment that can code for a 44-amino-acid leader peptide, and a sequence very similar to that of the attenuator of the trp operon. RNA transcripts from several bacterial strains were studied by S1 nuclease mapping. Under conditions leading to extensive enzyme synthesis there was a large production of transcript whose 5' end correlated with the putative promoter closer to the structural genes. At low levels of operon expression there was little transcript in the extracts and both promoters appeared to serve as initiation sites. The results are interpreted in terms of transcriptional control of the pyrB-pyrI operon according to an attenuation model that differs in novel ways from the mechanisms proposed for the regulation of amino acid biosynthesis.